The impact of fiscal policy and inflation on national saving: the Italian case - MODIGLIANI, F.; JAPPELLI, T.; PAGANO, M. (PSL Quarterly Review, 2013)
Apart from income there are two other main influences on national savings: fiscal policy and inflation. The authors construct a model of the Italian economy to analyse the impact of these two related variables. It is concluded that past government deficits have produced a proportional reduction in national saving. Since the early 1960s national savings have declined by nearly 9 percentage points, of which 3.6 percentage points can be accounted for by a 4 per cent increase in the government's deficit. The results regarding the impact of inflation are not definite, and no conclusion is drawn. JEL: E21, E31, E62